Antibody-Dependent Effector Functions Against HIV Decline in Subjects Receiving Antiretroviral Therapy - Madhavi, Vijaya; Ana-Sosa-Batiz, Fernanda E.; Jegaskanda, Sinthujan; Center, Rob J.; Winnall, Wendy R.; Parsons, Matthew S.; Ananworanich, Jintanat; Cooper, David A.; Kelleher, Anthony D.; Hsu, Denise; Pett, Sarah; Stratov, Ivan; et al. (The Journal of infectious diseases, 2015)
Background. Combination antiretroviral therapy (cART) effectively controls human immunodeficiency virus (HIV) infection but does not eliminate HIV, and lifelong treatment is therefore required. HIV-specific cytotoxic T lymphocyte (CTL) responses decline following cART initiation. Alterations in other HIV-specific immune responses that may assist in eliminating latent HIV infection, specifically antibody-dependent cellular cytotoxicity (ADCC) and antibody-dependent phagocytosis (ADP), are unclear. Methods. A cohort of 49 cART-naive HIV-infected subjects from Thailand (mean baseline CD4 count, 188 cells/μL; mean viral load, 5.4 log₁₀ copies/mL) was followed for 96 weeks after initiating cART. ADCC and ADP assays were performed using serum samples obtained at baseline and after 96 weeks of cART. Results. A 35% reduction in HIV type 1 envelope (Env)-specific ADCC-mediated killing of target cells (P < .001) was observed after 96 weeks of cART. This was corroborated by a significant reduction in the ability of Env-specific ADCC antibodies to activate natural killer cells (P<.001). Significantly reduced ADP was also observed after 96 weeks of cART(P=.018). Conclusions. This longitudinal study showed that cART resulted in significant reductions of HIV-specific effector antibody responses, including ADCC and ADP. Therapeutic vaccines or other immunomodulatory approaches may be required to improve antibody-mediated control of HIV during cART.